An introduction to radiation protection in medicine - Trapp, Jamie V.; Kron, Tomas (Series in medical physics and biomedical engineering., 2008)
Covers the physical and biological background of the subject and addresses the medical situations where radiation is the tool to diagnose or treat human disease. This text examines the framework of radiation protection guidelines introduced by the ICRP, and introduces the concepts of a system of radiation protection in the workplace.010